202k views
1 vote
Simplify (0.00243)^-2/5 x (0.0009)^1/2

User Jacobra
by
5.8k points

2 Answers

3 votes

Answer:

1/3

Explanation:

(0.00243)^-2/5 x (0.0009)^1/2

= 1/(0.00243)^2/5 x (0.0009)^1/2

= 1/0.3² × 0.03

= 1/0.09 × 0.03

= 1/3

User Zac Delventhal
by
5.9k points
4 votes

Answer:

(0.00243)^-2/5 x (0.0009)^1/2

= (243/100000)^-2/5 x (9/10000)^(1/2)

= ((3/10)^5)^-2/5 x ((3/100)^2)^(1/2)

= (3/10)^-2 x (3/100)

=1/(3/10)^2 x (3/100)

= (100/9) x (3/100)

= (1/3)

Hope this helps!

:)

User Adir Kandel
by
6.4k points